If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1x+10=-9+8x+4
We move all terms to the left:
-1x+10-(-9+8x+4)=0
We add all the numbers together, and all the variables
-1x-(8x-5)+10=0
We get rid of parentheses
-1x-8x+5+10=0
We add all the numbers together, and all the variables
-9x+15=0
We move all terms containing x to the left, all other terms to the right
-9x=-15
x=-15/-9
x=1+2/3
| 12=3/8v | | 5n-6=n+10 | | 16t-8t=8 | | 14d-3-2d=109 | | 250+25x=0+50x | | c=c2-4 | | -3x-49=4(x+7) | | 3m-m=16 | | c=c2-8 | | -2(-8k-1)=-37+3k | | 2x-×/14=2x-4/6 | | 5r-4r=12 | | 48n=-4 | | 64/16=18.5/w | | 6(1-7n)=-30-6n | | 10x+4x=31 | | 2x-4=10x-32 | | 18v-8v=20 | | -16-(-t)=-445 | | 5(u+4)-8u=4 | | -2=14+4x | | 1.8+7n=9.5+-4 | | 3(1x+2)=2x | | 2x-4=10x+36 | | 18=x/5+13 | | 3-5x=40 | | 3x+27x-1=6(5x+9 | | 15+q6=-21 | | 83=5+6(1+3n) | | -2+6(x+2)=1-3(x-5)+3x | | -2(×+3)=4x-3 | | 2x-18=136 |